2012
DOI: 10.1099/ijs.0.027409-0
|View full text |Cite
|
Sign up to set email alerts
|

Tepidibacter mesophilus sp. nov., a mesophilic fermentative anaerobe isolated from soil polluted by crude oil, and emended description of the genus Tepidibacter

Abstract: A mesophilic, aerotolerant, endospore-forming, fermentative bacterium, designated strain B1T, was isolated from soil polluted by crude oil in the Karamay Oil Field, China. Cells were Gram-positive, rod-shaped, 1.1–1.6 µm wide and 2.3–4.7 µm long, and were motile by means of peritrichous flagella. Growth occurred at 10–40 °C and pH 6.0–8.9; optimal growth occurred at 28–32 °C and pH 7.3. The optimal concentrations of NaCl and sea salts for growth were 0.5 and 1 % (w/v), respectively. The strain was halotolerant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The genus Tepidibacter ( Firmicutes ) was proposed (Slobodkin et al 2003) with three reported type species i.e. Tepidibacter thalassicus, Tepidibacter formicigenes and Tepidibacter mesophilus (Tan et al 2012). Thus, the OTUs from Jakrem hot spring representing Tepidibacter ( Firmicutes ) possibly are the novel species with in this genus.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Tepidibacter ( Firmicutes ) was proposed (Slobodkin et al 2003) with three reported type species i.e. Tepidibacter thalassicus, Tepidibacter formicigenes and Tepidibacter mesophilus (Tan et al 2012). Thus, the OTUs from Jakrem hot spring representing Tepidibacter ( Firmicutes ) possibly are the novel species with in this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Psychrilyobacter produces H2 and acetate and has the ability to degrade hexahydro-1,3,5-trinitro-1,3,5-triazine and octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine, two nitramine explosives (Zhao et al, 2009). Tepidibacter was isolated from an oil field in China (Tan et al, 2012). Photobacteriumspecies show mercuric resistance (Reyes et al, 1999), are stable in biodiesel production at high methanol concentrations (Yang et al, 2009) and have high oil emulsification activity (Ryu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The former two species are thermophilic and isolated from hydrothermal vents, but the latter one is mesophilic and isolated from soil contaminated by crude oil. T. mesophilus strain JCM 16806 T is anaerobic, aerotolerant, endospore forming, and fermentative; optimal growth occurred at 28 to 32°C ( 3 ).…”
Section: Genome Announcementmentioning
confidence: 99%